SEROPREVALENCE OF CYTOMEGALOVIRUS INFECTION IN PRE- MARITAL WOMEN IN SOME BAGHDAD HOSPITALS - Al-azzawi, Raghad (Iraqi Journal of Science, 2024)
One hundred and sixty one serum samples collected from pre-marital women in Baghdad province, without any clinical evidence of cytomegalovirus (CMV) infection, were screened for the presence of IgG and IgM antibodies against CMV by ELISA test. The IgG antibodies were detected in 58 which gave prevalence rate of 36%, while the IgM antibodies were detected in 16 (9.9%). The number of both IgG and IgM sero positive was 50 (31.1%) and the number of both IgG and IgM sero negative (control) was 37 (23%). rising in seropositivity was observed with young women, reaching to maximum of 46.6% in age group 15-19 years.While the lower percentage 9(5.6%) showed in the age group of (30-35) years. Seroprevalence rate was also found to be more in women from urban area than those from rural area, and the difference was statistically highly significant (p > 0.01).